PEMBERDAYAAN BERBASIS MASYARAKAT PEDESAAN DI ERA 4.0 MENUJU ERA 5.0 MELALUI PENGEMBANGAN DIGITALISASI PEDESAAN POSYANDU REMBULAN - Jumati, Nurleila; Agustin, Ardianti; Sari, Mamik Usniyah; Ardliyanto, Arif; Rachmania, Risca Ayu; Azizah, Aini Nur; Sari Wulan, Dyah Puspita Indah Budi; Putra Pratama, Muhammad Rafli; Setiawan, Rio; Lailiyah, Alfu Fitrotul (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2024)
The disruption of the 4.0 era leading to the Society 5.0 Era has created a new order that is more focused on society. The problems faced by the people of Bulangkulon Village are serious health problems faced by teenagers aged 18-26 years and early marriage and divorce. These problems are a shared responsibility of the community that must be resolved. The purpose of Community Partnership Empowerment (PKM) is to design and build a digital service management information system (SIM) so that teenagers in Bulangkulon Village can participate in services at the Rembulan Posyandu which improves the documentation process for physical and mental health checks, as well as training and mentoring for cadres to increase their capacity. The implementation method consists of socialization, FGD training, mentoring and partnerships. The results of the implementation of the activities are 1) coordination of program implementation with partners and stakeholders; 2) dissemination of programs and TTG and procurement of facilities and infrastructure: website and website usage training; 3) Recruitment - Selection and training for Rembulan Posyandu Cadres: a) organizational management; b) use of basic health check equipment; c) psychological first aid; d) adolescent sexual reproduction; e) socialization of drug abuse prevention; 4) sustainability of the Posyandu Rembulan program with the existence of a digitalization and counseling guidebook. The impact of the activity is an increase in the capacity of Posyandu Rembulan cadres, namely the average ability and skills of: 70% in the use of basic physical health check equipment and knowledge related to Posyandu Remaja, 50% related to the Posyandu Rembulan website and SIM, 35% knowledge and skills of peer counselors and an increase in quantity of 236% in the number of Posyandu Rembulan cadres. Thus, Posyandu Rembulan can become a Lembaga Kemasyarakatan Desa (LKD).